Características fisicoquímicas de los gases y partículas contaminantes del aire. Su impacto en el asma (2012)
ABSTRACT: Asthma is a multifactorial disease characterized by an inflammatory process that affects the airways. Its epidemiological increase in recent years seems to be mainly due to environmental factors. Increase in the concentration of air pollutants, secondary to the release of gases and small particles produced by the combustion of petroleum products, cigarette smoke and other anthropogenic sources, seems to have a strong association with the increase of allergic diseases both as triggers of asthma exacerbations, and as possible mediators in the onset of asthma and rhinitis, and in the sensitization to aeroallergens. In this article a review is presented on the main characteristics of gases and particles that have been considered risk factors for the development of asthma.